Hubungan Motivasi Berprestasi dengan Prokrastinasi Akademik pada Mahasiswa Program Studi Kedokteran Universitas Sebelas Maret - Sheilla Elfira San Pambayun; Suyatmi .; Leli Saptawati (Fakultas Kedokteran Universitas Sebelas Maret Surakarta, 2014)
Background: Academic procrastination is an educational and psychological problem that has negative effects for students. One of the factors that influence academic procrastination is the existence of achievement motivation. Students who have a high achievement motivation level will be highly motivated to finish their homework immediately, increased their skills, and interested in challenges. This study aimed to determine the correlation between academic procrastination and achievement motivation level in Medical Student of Sebelas Maret University. Methods: This study was an observational study with cross sectional approach on October 2014 in Faculty of Medicine, Sebelas Maret University. Total sampling of 173 students were included in this study. The data were obtained using Suyatmis Achievement Motivation Scale (2002) and Ahmainis Academic Procrastination Scale. The obtained data was analyzed using Spearmans rank correlation through SPSS 20.00 for Windows. Results: This study showed the average score of achievement motivation level was 14711.20, and the average score of academic procrastination was 84.0611.86. Spearmans rank correlation test showed Spearmans correlation coefficient (r) about -0.540 with significance level = 0.000 (p < 0.05). Conclusions: There was a moderate negative correlation and statistically significant between academic procrastination and achievement motivation level in Medical Student of Sebelas Maret University. Keywords: Achievement Motivation, Academic Procrastination, Medical Students